Appointment of Judicial Officer (International Journal of Innovative Research in Engineering & Management, 2021)
The three pillars of India's democratic system are the  legislative, administration, and judicial, with their respective  authorities and duties explicitly defined in the constitution.  However, the debate rages on, particularly when it comes to the  nomination of judges by the administration and judiciary.  Following the adoption of the Constitution, the administration  had a major voice in appointing judges. Later, the judiciary  interpreted the Constitutional requirements and created the  collegiums system, which limits the executive's role in  appointing judges to the higher courts. The judiciary's standing  was reinforced by the removal of the executive role. The  purpose of this article is to analyze the Constitutional Provision,  the function of the executive branch, as well as the importance  of legal interpretations in the selection of justices.
Keywords: Constitution; Executive; Judicial Interpretation; Judicial Appointment Commission